Fuel Switching Impacts of the Industry Sector under the Clean Development Mechanism: A General Equilibrium Analysis of Iran - Ashena, Maliheh; Sadeghi, Hossein; Yavari, Kazem; Najarzadeh, Reza (International Journal of Energy Economics and Policy, 2016)
The importance of international cooperation in reducing the Green House Gas (GHG) has been widely recognized. The primary tool for involving developing countries in carbon reduction without hindering their development is the clean development mechanism. In order to simulate numerically the impact of the Iran clean energy development of the industrial sector under the CDM, a computable general equilibrium (CGE) model is used. The numerical simulations reveal the growth potential and sustainable development benefits that represent the CDM for Iran, though the environmental impact in terms of carbon emission of sectors appears broadly mixed. Based on results some sectors benefit from these clean investment flows -including industry- other sectors show carbon emission increases, but the overall emission of the economy decrease and results in lower environmental costs in green GDP. Keywords: Clean Development Mechanism, Computable General Equilibrium, Industry Sector, Iran. JEL Classifications: D58, O13, Q56.